Ḍô. Āmbeḍakarāñcyā sahavāsāta - Kharāta, Śaṅkararāva Rāmacandra (Ināmadāra Bandhu Prakāśana, 1982)
Reminiscences of the author's association with Bhimrao Ramji Ambedkar, 1892-1956, Indian social reformer and political leader.